IL‐27 Inhibits Lymphatic Endothelial Cell Proliferation by STAT1‐Regulated Gene Expression. (9th August 2013) - Nielsen, Sebastian Rune; Hammer, Troels; Gibson, Josefine; Pepper, Michael S.; Nisato, Riccardo E.; Dissing, Steen; Tritsaris, Katerina
Abstract Objective IL‐27 belongs to the IL‐12 family of cytokines and is recognized for its role in Th cell differentiation and as an inhibitor of tumor angiogenesis. The purpose of this study was to investigate the effect of IL‐27 on proliferation of lymphatic endothelial cells to gain insight into the interplay between the immune system and development of the lymphatic system. Methods IL‐27‐stimulated signal transduction in human dermal lymphatic endothelial cells was measured by western blotting and synthesis of CXCL10 and CXCL11 by use of RT‐PCR and ELISA. Proliferation was measured using MTT and BrdU kits and the role of STAT1 and chemokines was determined by use of siRNA and recombinant proteins. Results Stimulation of lymphatic endothelial cell cultures with IL‐27 induced JAK dependent phosphorylation of STAT1 and STAT3 and inhibited lymphatic endothelial cell proliferation and migration. Expression of CXCL10 and CXCL11, both STAT1 target genes, was profoundly up‐regulated upon IL‐27 stimulation, and recombinant CXCL10 and CXCL11 inhibited FGF‐2‐induced proliferation in vitro. siRNA targeting of STAT1 almost completely abrogated CXCL10 and CXCL11 expression as well as the proliferative effect of IL‐27. Conclusions IL‐27 function as an anti‐lymphangiogenic regulator in vitro by up‐regulating chemokines and interfering with the mitogenic effect of growth factors through STAT1 activation.